2022
DOI: 10.3390/su14052999
|View full text |Cite
|
Sign up to set email alerts
|

Economic Effects of Ecological Compensation Policy in Shiyang River Basin: Empirical Research Based on DID and RDD Models

Abstract: In order to achieve the sustainable development of ecological resources and social economy in the Shiyang River Basin, a series of Ecological Compensation policies have been implemented in the basin. This study takes these policies as an opportunity to design an experiment. The nine counties (districts) affected by these policies are used as the experimental samples, and the period from 2000 to 2019 is the experimental period. The difference-in-differences method is used to study the effect of the series of Ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…Similarly, in the context of government land violations, studies analyze the theoretical basis for illegal actions by local governments and governance approaches based on different needs, behavioral motivations, and governance instruments. Additionally, in grassroots social governance 4 , 27 , 29 , research explores the collaboration of multiple actors through co-construction, co-management, and resource sharing. In the realm of carbon–neutral governance, studies 15 , 16 , 28 , 30 , 31 address the power-rights imbalance between the government, enterprises, and the public, and propose a “trinity” governance approach encompassing government-led governance, enterprise responsibility, and active public participation.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in the context of government land violations, studies analyze the theoretical basis for illegal actions by local governments and governance approaches based on different needs, behavioral motivations, and governance instruments. Additionally, in grassroots social governance 4 , 27 , 29 , research explores the collaboration of multiple actors through co-construction, co-management, and resource sharing. In the realm of carbon–neutral governance, studies 15 , 16 , 28 , 30 , 31 address the power-rights imbalance between the government, enterprises, and the public, and propose a “trinity” governance approach encompassing government-led governance, enterprise responsibility, and active public participation.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The diversified forms of ecological compensation include water rights trading, emissions trading and eco-industry 5 , 6 , reflecting both the market mechanism and the role of government and social organizations. The practice and theoretical research of China’s diversified ecological compensation pursue the combination of government, market and social forces, but in practice, market mechanisms and social organisations are still not sufficiently involved, which is also the direction of development 22 , 29 , 42 . In general, theoretical research on diversified ecological compensation in China is relatively rich, but practice is relatively backward, and needs to be explored in depth in terms of institutions, implementation paths and cases 30 , 31 .…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…These measures include biological indicators such as vegetation greening trend patterns and physical indicators such as top-layer soil properties, landscape change, etc. [44][45][46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…Another important aspect is climatic factors, where climate change brings changes in precipitation, which in turn affects the water cycle [ 29 ], thus changing the flow path time, peak flow, flow volume, and sand production [ 30 , 31 ]. Shang Haiyang [ 32 ] used ecological compensation policy as an opportunity to assess the impact of ecological compensation policy on economic development in the basin. Feng Lichao [ 33 ] analyzed the development trend and characteristics of these three subsystems in the Yellow River Basin based on a comprehensive evaluation system of the ecological environment subsystem, urbanization subsystem, and high-quality economic subsystem and found that during the study period, the comprehensive level of the Yellow River Basin showed a significant upward trend; urbanization and high-quality economic growth story is higher than the ecological environment level.…”
Section: Introductionmentioning
confidence: 99%